A Horizontally Acquired Transcription Factor Coordinates Salmonella Adaptations to Host Microenvironments - Nat F. Brown (American Society for Microbiology, 2014)
ABSTRACT The transcription factors HilA and SsrB activate expression of two type III secretion systems (T3SSs) and cognate effectors that reprogram host cell functions to benefit infecting Salmonella in the host. These transcription factors, the secretion systems, and the effectors are all encoded by horizontally acquired genes. Using quantitative proteomics, we quantified the abundance of 2,149 proteins from hilA or ssrB Salmonella in vitro. Our results suggest that the HilA regulon does not extend significantly beyond proteins known to be involved in direct interactions with intestinal epithelium. On the other hand, SsrB influences the expression of a diverse range of proteins, many of which are ancestral to the acquisition of ssrB. In addition to the known regulon of T3SS-related proteins, we show that, through SodCI and bacterioferritin, SsrB controls resistance to reactive oxygen species and that SsrB down-regulates flagella and motility. This indicates that SsrB-controlled proteins not only redirect host cell membrane traffic to establish a supportive niche within host cells but also have adapted to the chemistry and physical constraints of that niche. IMPORTANCE Expression of T3SSs typically requires a transcription factor that is linked in a genomic island. Studies of the targets of HilA and SsrB have focused on almost exclusively on T3SS substrates that are either linked or encoded in distinct genomic islands. By broadening our focus, we found that the regulon of SsrB extended considerably beyond T3SS-2 and its substrates, while that of HilA did not. That at least two SsrB-regulated processes streamline existence in the intracellular niche afforded by T3SS-2 seems to be a predictable outcome of evolution and natural selection. However, and importantly, these are the ﬁrst such functions to be implicated as being SsrB dependent. The concept of T3SS-associated transcription factors coordinating manipulations of host cells together with distinct bacterial processes for increased efficiency has unrealized implications for numerous host-pathogen systems.